The crime of stirring up hatred "between the problematic interpretation of Quranic texts and the effectiveness of national legislation - محمد, اياد خلف; حميد, سعد ناصر (Journal of Legal Sciences, 2019)
That the guarantee of respect for human rights and fundamental freedoms requires that all individuals within society be treated equally, and that the State, as the primary guarantor of the rights and freedoms of individuals, must provide adequate protection and combat any cause that would create discrimination or instigate a sense of hatred among the inhabitants of our beloved country, What we know is that the greatest factor that has lost lives is the hate factor throughout history, and the extremist groups have found no more effective reason than the creation of the hate factor. Hatred was the weapon for which many people were killed. The record of preparations for the drafting of the " The crime of genocide of 1948 "indicates that the perpetration of that crime" is in all cases attributable to the          rise of racial, national or religious hatred "and its call during the Second World War of 1939 (1945), which has prompted it to be included in internationally sanctioned acts.                                                                                                                                        Iraq, as one of the countries that ratified most of the international conventions on human rights, has through the Penal Code of 1969 criminalized any act or statement that would incite hatred and hatred among the sons of Iraq as an insult to human dignity and promised crimes against the internal security of the State. The penal code alone remains insufficient to ensure that discrimination and hostility that results in violence, murder and human rights violations are not carried.                 We sought to clarify the meaning of the crime of stirring hatred, its legal framework, its elements, and the impact of interpreting some of the Quranic texts in its commission. We reached a number of results, the most important of which are: seeking to activate Article 200 of the Iraqi Penal Code, In the freedom of expression and the prohibition of expressions that arouse feelings of hatred and hatred among the members of society. Emphasis must also be placed on educating the clergy not to promote extremist ideas and to emphasize the values ​​of love and tolerance affirmed by all religions